Prove.

\(\sec^2 a + cosec ^ 2 a = Sec^2 a. Cosec^2 a\)

Proof ::

LHS = sec^{2} A + cosec^{2} A

\(={1\over(cos^2A)}+{1\over(sin^2A)}={(sin^2A+cos^2A)\over(cos^2A sin^2A)}\)

\(={1\over(cos^2A sin^2A)}=sec^2A cosec^2A=RHS\)

Welcome to Brainiak.in , where you can ask questions and receive answers from other members of the community ,

There is many categories for every students CBSE , Maharashtra board , JEE , NEET and we will add more categories

and make brainiak one of the most loved community of students .

Get Your advertisement on Brainiak.in Buy Adspace

3.0k questions

2.5k answers

24 comments

341 users